Optimalisasi Tata Kelola Keselamatan Proses dan Perlindungan Lingkungan Melalui Pendekatan Sistem Manajemen Terpadu di Pabrik X - Achmad Zulfikar Badarudin Litiloly; Natalis Situmorang (Lembaga Pengembangan Kinerja Dosen, 2026)
This research aims to analyze and optimize process safety management and environmental protection at Factory X through an Integrated Management System IMS approach. Along with the increasing operational complexity of the manufacturing industry, the integration of process safety and environmental aspects has become crucial for mitigating the risk of major accidents and ecosystem pollution. This study employs a descriptive qualitative method with a case study approach, where evaluation is conducted based on the Plan-Do-Check-Act PDCA cycle, encompassing safety policy, organization, planning, performance evaluation, and improvement actions. The results indicate that although Factory X has established a formal policy foundation, operational effectiveness is still hindered by a lack of specialized competency within the HSE organization and the dominance of reactive performance indicators (lagging indicators). This study recommends the establishment of a specialized process safety unit, the utilization of digital technology for real-time asset monitoring, and the strengthening of incident reporting cultures to ensure continuous improvement. This optimization is expected to simultaneously reduce the potential risk of process failure and enhance compliance with environmental quality standards.